Mathematical modeling of the cardiac tissue. Issue 25 (12th October 2022) - Martynenko, A.; Zozulya, V. V.
Abstract: An improved mathematical model of soft heart tissue has been developed here. Nonlinear material equations were derived from the fundamental principles of nonequilibrium thermodynamics. The passive and active phases of cardiac tissue deformation are considered using the nonlinear theory of hyperelasticity. Elastic potentials for both phases are presented in a simple form convenient for numerical calculations. To take into account muscle contraction in the active phase of deformation, coupled equations of mechanochemical kinetics are obtained. The proposed model can be used for computer modeling of the heart and circulatory system.